Practices of Multiple Intelligence Instruction and Teaching Performance of Public Elementary School Teachers - Lennie M. Badajos; Crispina V. Diego (Philippine Social Science Journal, 2020)
Managing students in the classrooms with multiple intelligences is one of the tough issues teachers encounter. The practice of multiple intelligences instruction depends mainly on the teacher's performance in teaching. That is to challenge the students by setting high standards for further achievement and evaluate students' progress. The theory of Multiple Intelligence (MI) resonates with many educators. It gives an idea to create a relatively even distribution of students of different abilities and diverse educational needs. It has been found out that teachers who based their instructional practices on MI theory have more authentic classrooms, and students are more genuinely engaged in class. Hence, the paper describes the extent of multiple intelligences instructional practices and the level of teaching performance of the public elementary school. Likewise, it sought to determine the significant relationship between multiple intelligences instructional practices, teaching performance, and demographic profile of teachers.